Gas-Dynamic Temperature Stratification in the Leontiev Tube: Analytical Study and Numerical Modeling - R. S. Rudnik; A. F. Matveev; V. N. Kovalnogov (Вестник Дагестанского государственного технического университета: Технические науки, 2025)
Objective. The article is dedicated to the study of heat transfer processes in a Leontiev tube based on the principle of gas-dynamic temperature stratification. The objective of this work is to describe the mechanism of interaction between subsonic and supersonic flows and identify key parameters influencing stratification efficiency.Method. The study was conducted using an analytical approach and numerical modeling in the ANSYS Fluent environment. Temperature and velocity fields were visualized, and heat flow density was analyzed. The k−ω SST turbulence model was applied, enabling the consideration of complex gas flow characteristics in the tube.Results. The main heat transfer patterns were identified, including the effects of temperature and pressure differences between subsonic and supersonic flows, as well as the role of turbulent energy in enhancing heat exchange. It was established that the gas exiting the supersonic channel is heated compared to the inlet conditions, while the gas exiting the subsonic channel is cooled.Conclusion. The results can be used to improve the efficiency of heat exchange in industrial systems and to design heat recovery devices.